Mission drift : the unspoken crisis facing leaders, charities, and churches - Greer, Peter, 1975-; Horst, Chris; Haggard, Anna (Minneapolis, Minnesota : Bethany House Publishers, a division of Baker Publishing Group, 2014)
"The CEO of HOPE International shows organizations how to stay true to their Christian mission, and offers tools for getting back on track if 'drifting.'"--
Includes bibliographical references (p. 200-215)
Keywords: Mission of the church